PENGARUH KONSERVATISME AKUNTANSI TERHADAP ABNORMAL RETURN SAHAM PADA SAAT PENGUMUMAN SEASONED EQUITY OFFERINGS - Violetta, Vinny; Lestari, Jenjang Sri (Modus Journals, 2015)
This study aims to determine the efect of conservatism against abnormal stock returns during the announcement of Seasoned Equity Oferings (SEO) companies listed on the Stock Exchange. Tis study was conducted to see the efect of accounting conservatism towards abnormal return during the announcement of SEO. Tis study also uses the control variables of size and leverage. The sample in this company using the 39 companies listed on the Stock Exchange and ofering additional shares during 2011-2013. Results from the study showed that conservatism has a signifcant positive efect on abnormal stock returns during the announcement of SEO. Control variables leverage signifcant negative efect on abnormal stock returns during the announcement of SEO. While size has no efect on abnormal stock returns during the announcement of SEO.Keywords: abnormal return, conservatism, leverage, seasoned equity ofering